So many beginnings : a Little Women remix - Morrow, Bethany C. (Remixed classics, 2021)
At the Freedman's Colony of Roanoke Island, a haven for the recently emancipated, the four March sisters--Meg, Joanna, Bethlehem, and Amethyst--come into their own as independent young Black women together facing love, sickness, heartbreak, and new horizons.